Faktor-Faktor Determinan Pemilihan Karier Sebagai Akuntan Publik Dan Non-Akuntan Publik Pada Mahasiswa Akuntansi Di Perguruan Tinggi Swasta Surakarta - Isdihar, Niluh; Kristianto, Djoko (CV. Ulil Albab Corp, 2025)
The main problem in this study is the low interest of accounting students in Indonesia to choose a profession as a public accountant. This study aims to analyze financial rewards, professional recognition, social values and personality towards career choices as public accountants and non-public accountants for accounting students in Surakarta. This study used a sample of 120 accounting students at PTS Surakarta, the sampling technique used purposive sampling with the criteria of accounting students from PTS Accredited B and have passed the Auditing I and Auditing II courses. A questionnaire approach was utilized to collect data, and its validity and reliability were examined. Logistic regression analysis was employed as the data analysis method. (2) The results of the Exp (B) test indicate that the professional recognition factor has a dominant influence on the career choices of accounting students in Surakarta as public accountants. The study concludes that (1) “financial rewards, professional recognition, and social values have a significant effect on career choices as public accountants and non-public accountants for accounting students at PTS Surakarta, while personality does not have a significant effect.”